2016
DOI: 10.4314/agrosh.v15i2.8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Blood Rumen Content Mixture (BRCM) meal supplemented with yeast on the performance and gut microbial populations of broiler chickens

Abstract: One hundred and twenty (120)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…The source and processing of RD, diet formulation, and class and age of birds may all affect its utilisation by poultry. Contrary to previous reports on the beneficial effect of yeast (Oyedeji et al 2015) and xylanase (Mandey et al 2015) for supplementation of sun-dried RD meal, in this study enzyme supplementation provided no additional advantage. As earlier suggested, differences in the method of collection, processing, diet formulation and age of birds are all possible sources of variation in the performance of broilers fed RD-based diets.…”
Section: Growth Performancecontrasting
confidence: 96%
See 3 more Smart Citations
“…The source and processing of RD, diet formulation, and class and age of birds may all affect its utilisation by poultry. Contrary to previous reports on the beneficial effect of yeast (Oyedeji et al 2015) and xylanase (Mandey et al 2015) for supplementation of sun-dried RD meal, in this study enzyme supplementation provided no additional advantage. As earlier suggested, differences in the method of collection, processing, diet formulation and age of birds are all possible sources of variation in the performance of broilers fed RD-based diets.…”
Section: Growth Performancecontrasting
confidence: 96%
“…Up to 10% of the diet as sun-dried bovine blood-RD maintained the growth of pullet chicks (Adeniji and Balogun 2001) and broilers (Makinde et al 2008). Oyedeji et al (2015) recommended 10.5% of the diet as sun-dried bovine blood-RD for broiler growth. Odunsi et al (2004) observed that replacing 15% of dietary soybean meal with sun-dried blood-RD meal was the safest level for broiler growth.…”
Section: Growth Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Leaves and tender stem of cassava have been incorporated into broilers feed with encouraging result (Aderemi,et al, 2004). Oyedeji et al (2015) reported no detrimental effect of blood rumen content mixture (BRCM) meal supplemented with yeast on the performance and gut microbial populations of broiler chickens. Also Lamidiet al (2008) observed no adverse effect on the performance of chicken when 10% pineapple crush meal was used to replace maize.…”
Section: Introductionmentioning
confidence: 99%